CXCL1 Regulated by miR-302e Is Involved in Cell Viability and Motility of Colorectal Cancer via Inhibiting JAK-STAT Signaling Pathway - Chen, Biyin; Song, Li; Nie, Xiuzhen; Lin, Fangfeng; Yu, Zongyang; Kong, Wencui; Qi, Xiaoyan; Wang, Wenwu (Frontiers in Oncology, 2021)
Purpose: This study made a systemic description for the CXCL1-dependent regulatory mechanism in colorectal cancer (CRC). Methods: Bioinformatics methods were applied to obtain target mRNA CXCL1 and corresponding upstream miRNA. qRT-PCR and Western blot were performed to measure the levels of CXCL1 and miR-302e in CRC tissue and cells. Experiments including CCK-8, wound healing assay, Transwell invasion assay and flow cytometry were conducted to assess cell biological behaviors. Dual-luciferase reporter assay was carried out for verification of the targeting relationship between CXCL1 and miR-302e. The inhibitor AG490 of JAK-STAT signaling pathway was used to identify the functional mechanism of CXCL1/JAK-STAT underlying progression of CRC, and tumor xenograft experiments were performed for further validation. Results: CXCL1 was highly expressed in CRC tissue and cells, while miR-302e was poorly expressed. Silencing CXCL1 or overexpressing miR-302e could lead to inhibition of cell proliferation, migration, invasion but promotion of cell apoptosis of CRC. Besides, CXCL1 was identified as a direct target of miR-302e, and CXCL1 could reverse the effect of miR-302e on cell proliferation, migration, invasion and apoptosis. Furthermore, CXCL1 functioned on CRC cell biological behaviors via activation of JAK-STAT signaling pathway. Conclusion: CXCL1 could be regulated by miR-302e to inactivate JAK-STAT signaling pathway, in turn affecting cell proliferation, migration, invasion and apoptosis of CRC. Our result provides a potential therapeutic target for CRC treatment.